URGENSI PENDIDIKAN MULTIKULTURAL: SEBUAH JAWABAN ATAS PROBLEMATIKA PLURALITAS - Gregorius We'u Gerson (JIPD (Jurnal Inovasi Pendidikan Dasar), 2020)
ABSTRACT Plurality or pluralism is a real situation that must be accepted by all Indonesian people who are built on the basis of differences. These differences at some point can create conflict. Therefore, a solution or prevention is needed, namely multicultural education, so that plurality or pluralism can be maintained and accepted as an asset or wealth owned by the Indonesian nation. The aim is to maintain national harmonization and integration. The research method used is descriptive qualitative research method with reference to Milles and Huberman theory. Thus, the results obtained that multicultural education is problem solving in the midst of plurality or pluralism, which increasingly leads to something negative or fanaticism in various aspects or dimensions. The conclusion is plurality or pluralism is a social fact that must be accepted consciously and critically in order to create the condition of Indonesian human beings who are respectful, respectful, peaceful, secure, orderly, and share each other in order to improve the sovereign, fair and prosperous dignity of the nation and civilized. Key Words: Plurality, conflict, and multicultural education